The Role of Village Midwives in Reducing Stunting Rates in Children Under Two Years Old (BADUTA) - Shinta Oktarina; Idawati Idawati; Yuliana Yuliana (Institute of Computer Science (IOCS), 2022)
On the empirical fact that Gampong Ara succeeded in reducing the stunting rate in badutanya, in 2017, there were 13 cases and decreased to 4 cases in 2019 and in 2020 there were no more. The purpose of the study was to determine the role of village midwives in reducing stunting rates in children under two years old (baduta) in Gampong Ara, Kembang Tanjong District, Pidie Regency. This research uses a qualitative type of research with a case study design. The sample informants were 6 people, namely the Midwife of Ara Village, the Village Head or Keuchik Gampong Ara, the Cadre of the Gampong Ara Posyandu, 2 beneficiary communities (1 person with a history of stunting children and 1 more person with the risk of stunting) plus the Head of the Kembang Tanjong Health Center. The research time was held in April 2022. The results showed that village midwives in Gampong Ara have carried out their role in reducing stunting rates, but there are several aspects that are still not met. The conclusion is that the village midwife has carried out her role as an executor, manager, educator and researcher in the stunting reduction program in Gampong Ara, but not all of them are like helping childbirth, because the village midwife does not live in place and holds 3 villages as her midwife. Advice to policymakers, can work on development for the residence of village midwives in Gampong Ara, so that village midwives can carry out their total roles such as helping childbirth and allocating other village midwives so that Gampong Ara village midwives no longer hold 3 villages as their midwives, so that they can focus more on carrying out their role as village midwives in Gampong Ara. The midwife of Gampong Ara village is expected to continue to increase her role as a midwife.